Studi Sifat Fisik dan Kekuatan Tekan Material Komposit Serat Eceng Gondok dan Kulit Jagung - Ramadani, Andi Indra Wulan Sari; Latief, Muh. Fachrul (Peneliti.net, 2024)
The high demand for materials with unique properties such as composites, especially in increasingly massively produced structural applications, requires the industry to switch from synthetic fiber reinforced composites such as fiberglass to composites with natural fibers. The use of natural fibers as fillers not only considers their environmentally friendly properties but also the nature of natural fibers which tend to have low density so that they are expected to be able to provide unique physical and mechanical properties to engineered composite materials. This study examines how the physical properties and compressive strength of composites with epoxy matrices and two types of natural fiber fillers, namely water hyacinth and corn husks. The results of this study indicate that alkali treatment in the preparation of corn husk and water hyacinth fiber samples significantly affects the density, porosity and compressive strength of the resulting composites. In addition, the uniformity of fiber orientation and the number of fibers per unit area also contribute positively to the physical properties and compressive strength of natural fiber composite samples.